Gambaran Faktor yang Mempengaruhi Keluarga tetap Melakukan BAB di Sungai di Kota Blitar - Heni Novikasari (Journal of Ners and Midwifery, 2016)
Factors affecting the family still doing defecation in rivers such as the factors of knowledge, customs, infrastructure, and social support. Methods: The research design was descriptive. The population in this study was the family who still do defecate in the river in the city of Blitar as many as 511 families. Total sample was 102 families taken with quota sampling technique. The research instrument was in the form of a questionnaire. Result: showed 51% (52 families) had a good level of knowledge. 67.6% (68 families) had a habit less. 94.1% (96 families) with less infrastructure. 87.3% (89 families) said that social support from health workers and government in good category. It was caused by the bad habits of the family. Suggestions for health employees to continue to provide counseling that aimed to change the behavior of families and for community leaders provided infrastructure facilities around the family environment which still doing defecation in the river.